The effectiveness of the Sirius School for high school teachers - Acioly, Vitor; Velloso, Marcio; Santos, Antonio (Education and Development Research, 2024)
The Sirius School for High School Teachers (ESPEM) is an in-service program for high school science teachers. It is held at the National Center for Research in Energy and Materials in Campinas, in partnership with the Brazilian Society of Physics. The program aims to enhance the skills of science teachers in high schools, facilitate the exchange of knowledge between teachers from all over Brazil, and produce updated teaching materials that promote Brazilian science and technology. To investigate how ESPEM contributes to the training of basic education teachers, and to assess the effectiveness of the program, we employed various data collection methodologies in a qualitative research study. Our objectives were: i) to identify the expectations of the participating teachers, ii) to evaluate the products generated during the program, and iii) to measure the achievement of the main goals of ESPEM. To achieve these objectives, we analyzed the letters of intent submitted by the selected participants before the program began. During the program, we conducted participant observation. After the program, we conducted semi-structured individual interviews, and a focus group, and distributed questionnaires to the participants.